DC nanogrid for renewable sources with modular DC/DC LLC converter building block. Issue 5 (16th February 2017) - Cecati, Carlo; Khalid, Hassan Abdullah; Tinari, Mario; Adinolfi, Giovanna; Graditi, Giorgio
Abstract : Centralised electricity systems are being integrated by a multitude of small distributed generation clusters, called nanogrids, capable of ensuring full utilisation of renewable energy sources, high flexibility, efficiency and improved reliability of the power grid due to redudancy. In this study, small photovoltaic plants combined with energy storage systems represent a promising solution for full exploitation of renewable energies and for effective development of electromobility. The purpose of this study is two‐fold: first it deals with a DC nanogrid suitable for small energetic clusters such as residential or office buildings and consisting of photovoltaic arrays, fuel cells, electric vehicle charger stations, loads, then proposes a multifunctional full‐bridge DC/DC LLC resonant converter building block. The latter, while accepting large input/output ranges is suitable for photovoltaic and fuel cells energy conversion, electric vehicle recharging stations and other DC applications available in the nanogrid. Proposed power system can be interconnected with conventional AC grid through voltage source converter. After description of proposed nanogrid, some analyses are performed on its core element, i.e. the DC converter building block.